2019
DOI: 10.1016/j.ymthe.2018.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-coding RNA ECRAR Triggers Post-natal Myocardial Regeneration by Activating ERK1/2 Signaling

Abstract: Reactivating post-natal myocardial regeneration potential may be a feasible strategy to regenerate the injured adult heart. Long non-coding RNAs (lncRNAs) have been implicated in regulating cellular differentiation, but whether they can elicit a regenerative response in the post-natal heart remains unknown. In this study, by characterizing the lncRNA transcriptome in human hearts during the fetal-to-adult transition, we found that 3,092 lncRNAs were differentially expressed, and we further identified a novel u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 27 publications
0
83
0
Order By: Relevance
“…Adult mouse CMs were isolated from 10-week-old adult mice using a modified protocol as described. 35 Briefly, when the adult mouse was anesthetized, the heart was rapidly excised and mounted on a Langendorff apparatus. Then, the heart was perfused with calcium-free perfusion buffer (113 mM NaCl, 4.7 mM KCl, 0.6 mM KH 2 PO 4 , 0.6 mM Na 2 HPO 4 , 1.2 mM MgSO 4 , 10 mM Na-HEPES, 12 mM NaHCO 3 , 10 mM KHCO 3 , 0.032 mM phenol red, 30 mM taurine, 10 mM 2,3-butanedione monoxime [BDM], and 5.5 mM glucose) for 5 min, followed by the addition of 50 mL digestion buffer composed of 15,000 U of type II collagenase (Roche) and 50 μM CaCl 2 for 10 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult mouse CMs were isolated from 10-week-old adult mice using a modified protocol as described. 35 Briefly, when the adult mouse was anesthetized, the heart was rapidly excised and mounted on a Langendorff apparatus. Then, the heart was perfused with calcium-free perfusion buffer (113 mM NaCl, 4.7 mM KCl, 0.6 mM KH 2 PO 4 , 0.6 mM Na 2 HPO 4 , 1.2 mM MgSO 4 , 10 mM Na-HEPES, 12 mM NaHCO 3 , 10 mM KHCO 3 , 0.032 mM phenol red, 30 mM taurine, 10 mM 2,3-butanedione monoxime [BDM], and 5.5 mM glucose) for 5 min, followed by the addition of 50 mL digestion buffer composed of 15,000 U of type II collagenase (Roche) and 50 μM CaCl 2 for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…The animal studies were conducted as previously described. 35 , 40 Briefly, adult mice were intramyocardially injected at 3–5 sites with AAV9 vectors expressing circHipk3 or empty vectors (AAV9-circHipk3 or AAV9-vector) at a dose of 1,011 viral genome particles per mouse (approximately 30 μL) using an insulin syringe with a 30-gauge needle. For the infarcted mice, AAV9 was injected into myocardial tissue close to the infarct zone immediately after the left anterior descending coronary artery ligation.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to the above-mentioned lncRNAs several others have been shown to mediate cardiomyocyte proliferation mainly by perturbing miRNAs and direct binding to proteins [12,[24][25][26] *.…”
Section: Lncrnas In Cardiac Regenerationmentioning
confidence: 92%
“…In addition, further analysis revealed that E2F1 transcriptionally upregulates ECRAR. Therefore, E2F1-ECRAR-ERK1/2 form a positive feedback loop to drive CM proliferation [124].…”
Section: Lncrnas In Cardiac Regenerationmentioning
confidence: 99%